The teachings of Don Juan : a Yaqui way of knowledge - Castaneda, Carlos, 1931-1998 (Washington Square Press, 1998)
Castaneda's famous exploration of sorcery and the way of the warrior, learned from the mysterious native shaman Don Juan.